An investigation of the molecular signalling events which occur in cannabiniod-mediated neuronal apoptosis - Gowran, Aoife (Trinity College (Dublin, Ireland). Department of Physiology, 2008)
The plant-derived cannabinoid Δ9-Tetrahydrocannabinol, is the predominant psychoactive moiety of cannabis and exerts a variety of psychological and physiological effects in humans. Previous investigations in this laboratory have shown that Δ9-Tetrahydrocannabinol (5 μM) induces apoptosis in cortical neurones via signalling through the cannabinoid receptor type 1. The phosphorylation of the tumour suppressor protein, p53 at serine residue 15 is a critical step in stabilising p53 and promoting p53-induced apoptosis. I report that Δ9-Tetrahydrocannabinol activates p53 by inducing the phosphorylation of serine residue 15, which was mediated by the stress activated protein kinase, c-jun N terminal kinase 1. Furthermore, Δ9-Tetrahydrocannabinol induced the translocation of phosphorylated-p53 ser15 to the lysosomal membrane; an event that coincided with Δ9-Tetrahydrocannabinol-induced lysosomal membrane destabilisation. Δ9-Tetrahydrocannabinol also induced the selective translocation of cathepsin-D, a lysosomal protease which was required for Δ9- Tetrahydrocannabinol-induced caspase-3 activation and DNA fragmentation. Depleting neurones of p53 using small interfering RNA inhibited Δ9-Tetrahydrocannabinol- induced lysosomal membrane destabilisation and DNA fragmentation, indicating that p53 signalling is pivotal in Δ9-Tetrahydrocannabinol-induced lysosomal branch of neuronal apoptosis. Additional evidence for the proclivity of Δ9-Tetrahydrocannabinol to regulate p53 signalling was demonstrated by the alterations observed in the p53 post translational modifying proteins, murine double minute 2 and small ubiquitin modifier 1. The observed changes in these p53 regulatory proteins could potentially increase the activity of p53, thus promoting Δ9-Tetrahydrocannabinol-induced p53-dependent neuronal apoptosis.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin